CE‐MS‐based proteomics in biomarker discovery and clinical application. Issue 3 (24th March 2015) - Pontillo, Claudia; Filip, Szymon; Borràs, Daniel M.; Mullen, William; Vlahou, Antonia; Mischak, Harald
Abstract : CE‐MS is applied in clinical proteomics for both the identification of biomarkers of disease and assessment of biomarkers in clinical diagnosis. The analysis is reproducible, fast, and requires only small sample volumes. However, successful CE‐MS analysis depends on several critical steps that can be consolidated as follows: (i) proper sample preparation and fractionation, (ii) application of suitable capillary coating and appropriate CE‐MS interfaces, to ensure the reproducibility and stability of the analysis, and (iii) an optimized clinical and statistical study design to increase the chances for obtaining clinically relevant results. In this review, we cover all these aspects, and present several examples of the application of CE‐MS in clinical proteomics.